Why oral palliative care takes a backseat? A national focus group study on experiences of palliative doctors, nurses and dentists - Munikumar Ramasamy Venkatasalu; Zaidah Rizidah Murang; Hajah Asmah binti Haji Husaini; Deeni Rudita Idris; Jagjit Singh Dhaliwal (Wiley, 2020)
Abstract Aim Poor oral care among frail older people at the end of life endangers quality of life. However, only few dying people have access to oral palliative care services. Therefore, this study aimed to investigate oral palliative care practices and referral patterns for palliative patients in the Brunei healthcare settings. Design An exploratory qualitative study. Methods Five focus groups were conducted among palliative care nurses (N = 7), palliative medicine doctors (N = 4), dentists (N = 6), oncologists (N = 4) and oncology nurses (N = 4). Verbatim was analysed using qualitative thematic analysis. Results Analyses revealed four distinct themes emerging as current oral palliative care assessment and referral practice in the Brunei healthcare settings: "taking a back seat," "opportunistic oral care," "they refused and refused" and "challenging healthcare resources and oral palliative care."